Edukasi Kesehatan dalam Meningkatkan Defisit Pengetahuan tentang Pencegahan Penularan Tuberkulosis (TBC) - Andriani, Wiwiek Retti; Hidayat, Bagus Syahrian (Universitas Sultan Ageng Tirtayasa, 2024)
Pulmonary tuberculosis is a contagious disease caused by an infection of the Mycobacterium tuberculosis bacteria. The cause of transmission in pulmonary TB patients is low knowledge due to a lack of information. The purpose of the research is to provide nursing care to pulmonary TB clients with a knowledge deficit in transmission prevention in the working area of Sukorejo Health Center, Ponorogo. The research method applied is descriptive with a case study form involving one participant. Data collection techniques through interviews and questionnaires on knowledge of TB transmission prevention. The assessment results showed that the client had a low level of knowledge, and the client asked about TB, especially in preventing transmission. The nursing diagnosis established is knowledge deficit. Nursing intervention according to SIKI: Health education and disease process education implemented over 5 days using lecture methods, through video media and leaflets. The established outcome criteria are an increased level of knowledge, indicated by the client's ability to answer the tuberculosis transmission prevention knowledge questionnaire and achieve a good level of knowledge, be able to explain the material presented, and apply the material in their life. After being implemented for 5 days, the results showed that the participants' knowledge, which initially fell into the poor knowledge category (46%), improved to the good knowledge category (86%). Factors for success in providing education can include family support by motivating patients to consistently take their medication and follow up when it runs out, and monitoring patients to ensure they maintain behaviors that reduce the risk of transmission.